Formation of Early Childhood Religious Character Through Religious Activities in School - Toifur; Setiawati , Rahmah; Ali , Musyafa (Jurusan PG-PAUD Universitas Halu Oleo,, 2022)
religiosity becomes an inseparable part in the relationship between humans and the creator. The purpose of this study is to find out how to form the religious character of early childhood through religious activities in school. This research was conducted at Bina Insan Mandiri School Purwokerto Kindergarten. This research is field research or field research. The methods used by researchers in collecting data are interviews directly with teachers, observation of religious activities carried out by children during school and documentation in the form of pictures, and RPPH documents, and RPPM. In analyzing the data, researchers used miles and huberman techniques, starting with reducing data, presenting data and finally drawing conclusions and verification. The results of this study show that religious activities carried out by early childhood in order to form their character are amaliyah activities, such as praying, dhikr, dhuha prayer and others.